Preparation, Characterization, and Antioxidant Properties of Phycocyanin Complexes Based on Sodium Alginate and Lysozyme - Qiao, Bian-Wen; Liu, Xin-Tong; Wang, Chen-Xin; Song, Shuang; Ai, Chun-Qing; Fu, Ying-Huan (Frontiers in Nutrition, 2022)
In this study, phycocyanin-sodium alginate/lysozyme complex (PC-SLC) was prepared for the first time and characterized by UV spectroscopy, Fourier transform infrared spectroscopy (FT-IR), and circular dichroism spectroscopy (CD). The stability of PC-SLC under light, temperature, pH and simulated gastrointestinal fluid was investigated. The scavenging ability of the complexes against DPPH and ABTS radicals was determined. The results showed that the complex formed by the mass ratio of SA-LZM of 0.1 showed the highest PC encapsulation rate (89.9 ± 0.374%). The combination of SA and LZM changed the secondary conformation of PC. The PC-SLC complex shows an irregular spherical structure and the spheres are clustered together. Compared with phycocyanin (PC), its thermal stability was obviously improved, but it was still greatly influenced by light. It could exist stably in simulated gastric fluid (SGF) for 2 h and be slowly digested in simulated intestinal fluid (SIF), which helped to promote the absorption of nutrients in the intestinal tract. Meanwhile, the complex PC-SLC showed high scavenging ability for DPPH and ABTS radicals. It can be concluded that the complexes have good antioxidant activity. This study provides an idea for the construction of PC delivery system and makes it more widely used in food industry and other fields.